2018
DOI: 10.1016/j.rgmx.2017.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Caracterización del carcinoma hepatocelular en México

Abstract: Better surveillance methods are required to diagnose the disease at its early stages, but treatment still requires individual adaptation to each center's available resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Furthermore, no systematic national registry is accessible to confirm these findings. One study found that 6.1% of patients with HCC were attributable to HBV, although the etiology of HCC was not detected in 30.4% of patients [136]. Outside of Mexico, only one case of HCC was reported in a 12-year-old Japanese female infected with HBV genotype H isolate presenting a PreS2 deletion mutation.…”
Section: Hbv Infections In Cirrhosis and Hccmentioning
confidence: 99%
“…Furthermore, no systematic national registry is accessible to confirm these findings. One study found that 6.1% of patients with HCC were attributable to HBV, although the etiology of HCC was not detected in 30.4% of patients [136]. Outside of Mexico, only one case of HCC was reported in a 12-year-old Japanese female infected with HBV genotype H isolate presenting a PreS2 deletion mutation.…”
Section: Hbv Infections In Cirrhosis and Hccmentioning
confidence: 99%